Muhammed in the various world religious scriptures - Islamic Research Foundation (Mumbai : Islamic Research Foundation [production company] ; Kuala Lumpur : SABA Islamic Media [distributor])
The lectures by Dr. Zakir Naik in The Muslim Educational Association of Southern India on the topics of Muhammed, the prophet, in the various world religious scriptures
Speaker: Zakir Naik, Hajee Anaikar Abdul Shukoor
Keywords: Muhammad, -- Prophet, -- d. 632